2022
DOI: 10.1029/2022gh000636
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Burden of Heat‐Related Illness Morbidity Attributable to Anthropogenic Climate Change in North Carolina

Abstract: Since the mid-twentieth century, the frequency and duration of hot days have increased globally due to anthropogenic climate change (Hoegh-Guldberg et al., 2018). Global temperature is very likely to increase up to 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(78 reference statements)
0
6
0
1
Order By: Relevance
“…In recent years, bene ting from the Detection and Attribution Model Intercomparison Project (DAMIP) 28 , some studies [22][23][24] began to focus on attributing the impact of extreme temperature on population health to climate change and also further distinguish the contribution of human-induced climate change, to provide useful information to the international community and policymakers. A multi-country study showed that 1.56% of deaths in the warm season were caused by heat exposure, and 37.0% of these heat-related deaths could be attributed to global warming caused by human activities 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, bene ting from the Detection and Attribution Model Intercomparison Project (DAMIP) 28 , some studies [22][23][24] began to focus on attributing the impact of extreme temperature on population health to climate change and also further distinguish the contribution of human-induced climate change, to provide useful information to the international community and policymakers. A multi-country study showed that 1.56% of deaths in the warm season were caused by heat exposure, and 37.0% of these heat-related deaths could be attributed to global warming caused by human activities 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to establishing the association between extreme temperature exposure and health, further clarifying the health impact attributable to humaninduced climate change can inform the international community and policymakers of evidence-based risk management to reduce current and future health risks related to climate change. Previous studies have conducted attribution analyses related to extreme temperatures [22][23][24] but been focused mainly on mortality or morbidity. A recent study has estimated the burden of preterm birth attributable to anthropogenic climate change in China 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Frame et al 20 estimated climate change-attributable insured costs of major flooding events in Aotearoa New Zealand based on the aggregation of attributed costs from 12 major flooding events. Some recent papers have looked at counting mortality and morbidity from heatwaves and attributing these to climate change 39 41 .…”
Section: Methodsmentioning
confidence: 99%
“…One of the most common approaches to impact attribution directly combines climate trend attribution and impact simulations in a single analysis. For example, a number of studies have examined how long-term temperature trends have led to long-term changes in heat-related mortality (Chapman et al, 2022;Stuart-Smith et al, 2023;Vicedo-Cabrera et al, 2021) and morbidity (Puvvula et al, 2022), as well as a number of issues related to child health, including preterm births (Zhang et al, 2022), low birth weight (Zhu et al, 2023), and childhood malaria (Carlson et al, 2023). Other studies have examined the contribution of human-caused climate change to global trends in poverty (Callahan & Mankin, 2022;Diffenbaugh & Burke, 2019) and food systems vulnerability (Dasgupta & Robinson, 2022;Ortiz-Bobea et al, 2021).…”
Section: Trend-to-trend Impact Attributionmentioning
confidence: 99%
“…manuscript submitted to Earth's Future Although many studies make a high-level distinction between attribution (understanding of past or present human-caused climate change) and projection (exploration of possible future scenarios for human-caused climate change), the boundary between the two is necessarily blurry. For example, as a complement to an existing trend-to-trend impact attribution analysis, researchers can also run forward-facing projections under different future emissions pathways through midor end of century (Carlson et al, 2023;Chapman et al, 2022;Puvvula et al, 2022). Similarly, a growing number of probabilistic event attribution studies already include a third projection scenario (often the policy-relevant targets of 1.5 or 2 °C of warming); this can be a valuable tool for framing risk, especially if the probability of event occurrence accelerates at higher levels of warming (i.e., a "rare" event in today's human-altered climate may be common under future warming levels).…”
Section: Projection or "Reverse" Attributionmentioning
confidence: 99%